Retinoids, rexinoids and their cognate nuclear receptors: character and their role in chemoprevention of selected malignant diseases - Brtko, Julius (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2007)
BACKGROUND: Retinoids, rexinoids and their biologically active derivatives are involved in a complex arrangement of physiological and developmental responses in many tissues of higher vertebrates. Both retinoids and rexinoids are either natural or synthetic compounds related to retinoic acids that act through interaction with two basic types of nuclear receptors belonging to the nuclear receptor superfamily: All-trans retinoic acid receptors (RARalpha, RARbeta, and RARgamma) and retinoid X receptors (RXRalpha, RXRbeta and RXRgamma) as retinoid-inducible transcription factors. AIM: Summarization of selected effects of biologically active natural or synthetic retinoids and rexinoids and their exploitation in chemoprevention of various types of cancer. RESULTS: Retinoid receptors play a role as ligand-activated, DNA-binding, trans-acting, transcription-modulating proteins involved in a general molecular mechanism responsible for transcriptional responses in target genes. They exert both beneficial and detrimental activity; they have tumour-suppressive activity but on the other hand they are teratogenic. A number of nuclear receptor selective retinoids and rexinoids, have been successfully tested using a variety of cell lines or animal models. Retinoids inhibit carcinogenesis, suppress premalignant epithelial lesions and tumour growth and invasion in a variety of tissues. CONCLUSIONS: Natural and synthetic retinoids exert important biological effects due to their antiproliferative and apoptosis-inducing effects. They are also known to cause redifferentiation or to prevent further dedifferentiation of various tumour tissues.
Keywords: Animals; nádory; lidé; receptory kyseliny retinové; retinoidní X receptory; retinoidy; Neoplasms; Humans; Receptors, Retinoic Acid; Retinoid X Receptors; Receptors, Cytoplasmic and Nuclear; receptory cytoplazmatické a nukleární; Retinoids; zvířata